Towards a global land surface climate fiducial reference measurements network - P. W. Thorne; H. J. Diamond; B. Goodison; S. Harrigan; Z. Hausfather; N. B. Ingleby; P. D. Jones; J. H. Lawrimore; D. H. Lister; A. Merlone; T. Oakley; M. Palecki; et al. (International Journal of Climatology, 2018)
There is overwhelming evidence that the climate system has warmed since the instigation of instrumental meteorological observations. The Fifth Assessment Report of the Intergovernmental Panel on Climate Change concluded that the evidence for warming was unequivocal. However, owing to imperfect measurements and ubiquitous changes in measurement networks and techniques, there remain uncertainties in many of the details of these historical changes. These uncertainties do not call into question the trend or overall magnitude of the changes in the global climate system. Rather, they act to make the picture less clear than it could be, particularly at the local scale where many decisions regarding adaptation choices will be required, both now and in the future. A set of high‐quality long‐term fiducial reference measurements of essential climate variables will enable future generations to make rigorous assessments of future climate change and variability, providing society with the best possible information to support future decisions. Here we propose that by implementing and maintaining a suitably stable and metrologically well‐characterized global land surface climate fiducial reference measurements network, the present‐day scientific community can bequeath to future generations a better set of observations. This will aid future adaptation decisions and help us to monitor and quantify the effectiveness of internationally agreed mitigation steps. This article provides the background, rationale, metrological principles, and practical considerations regarding what would be involved in such a network, and outlines the benefits which may accrue. The challenge, of course, is how to convert such a vision to a long‐term sustainable capability providing the necessary well‐characterized measurement series to the benefit of global science and future generations.

Effect of changes in temperature scales on historical temperature data - P. Pavlasek; A. Merlone; C. Musacchio; Å. A. F. Olsen; R. A. Bergerud; L. Knazovicka (International Journal of Climatology, 2016)
Temperature has always been a central quantity in meteorology and plays a key role in weather forecast and climate determination. Long temperature series are a useful tool both as a direct indicator of global climatic trends and as input to climate models. However, ensuring the quality of the data records is challenging, with issues arising from the wide range of sensors used, how the sensors were calibrated, and how the data were recorded and written down. In particular, the very definition of the temperature scales has evolved. While the temperature scales have always been tied to phase transitions of substances such as the freezing and boiling points of water, the temperatures assigned to those phase transitions have been revised occasionally when new sensors and measuring techniques suggested discrepancies between the temperature scales and thermodynamic temperature. Invariably this has led to alterations in the reference scales of temperature that give rise to biases when compiling historic temperature records, an issue that appears to be neglected in the meteorological literature. The present work deals with this issue for 20th century data by proposing a mathematical model to allow the conversion from historical scales to the International Temperature Scale of 1990 (ITS‐90). This work also presents the implementation of this mathematical model into a software tool, which can convert large files of historical records to the ITS‐90. The correction equation is applied to example observations, and it is found that the correction becomes an issue in special cases involving aggregated temperature data. However, the corrections are significantly smaller than the global warming trend seen in the 20th century. The corrections applied have shown a level of change, which has not significantly affected the global warming trend.

Comparative analysis of the influence of solar radiation screen ageing on temperature measurements by means of weather stations - G. Lopardo; F. Bertiglia; S. Curci; G. Roggero; A. Merlone (International Journal of Climatology, 2014)
Solar radiation screens play a key role in automatic weather stations ( AWS ) performances. In this work, screen ageing effects on temperature measurements are examined. Paired temperature observations, traceable to national standards and with a well‐defined uncertainty budget, were performed employing two naturally ventilated weather stations equipped with identical sensors and different only for their working time. Three different tests were carried out employing different aged AWSs : a 5‐year‐old AWS ( AWS5 ) was compared with a new device ( AWS0 ), a 1 year old ( AWS1 ) was compared with both a 3 years old ( AWS3 ) and a new one devices ( AWS00 ). Due to solar and weather conditions exposure a degradation of the screen reflective coating is evident for the older AWSs (5 and 3 years old) and so a qualitative estimation of how different conditions of ageing affect the temperature drift was done. During the comparison 0 to 5 and 1 to 3‐year‐old screens, significant temperature differences were recorded at different times of the day. The differences, wider than the uncertainty amplitude, demonstrate a systematic effect. The temperature measured with the older screen is larger, and the maximum instantaneous difference was 1.63 °C (for 0–5 years comparison) in daytime hours. During night‐time the two AWS 's measure the same temperature (within the uncertainty amplitude). This behaviour, increasing with increasing solar radiation intensity and decreasing with increasing wind speed, is attributed to a radiative heating effect. The screen ageing has compromised the shield effectiveness introducing a significant change in the temperature evaluation. The experimental results of a further comparison, between 0‐ and 1‐year‐old screens, confirm the same conclusion showing a negligible ageing effect, within the uncertainty amplitude.